The discourse on the emancipation of women during the armed internal conflict in Peru: memories of the PCP-SL women - López López, Fiorella (2017)
This article analyzes the discourse on the emancipation of women that the Communist Party of Peru-Shining Path (PCP-SL) spread towards achieving its armed political project in the Peruvian context. The objectives of this studyare to determine the reasons that led the ideology of the PCP-SL to convene a large number of women and if it really meant a liberation or a significant change in terms of gender structures. The sources used are bibliographic texts, PCP-SL documentation, testimonies of the Peruvian Truth and Reconciliation Commission (TRC) and dialogues with women who have been sentenced and imprisoned for the crime of terrorism at Santa Monica maximum security prison. This research finds that even though the PCP-SL did not introduce an integral gender policy, it allows a different kind of participation for women, the creation of new feminine roles and a significant change in the life of many of them.